The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjhci-2020-100294
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure and operating processes of PIONEER, the HDR-UK Data Hub in Acute Care and the workings of the Data Trust Committee: a protocol paper

Abstract: IntroductionHealth Data Research UK designated seven UK-based Hubs to facilitate health data use for research. PIONEER is the Hub in Acute Care. PIONEER delivered workshops where patients/public citizens agreed key principles to guide access to unconsented, anonymised, routinely collected health data. These were used to inform the protocol.MethodsThis paper describes the PIONEER infrastructure and data access processes. PIONEER is a research database and analytical environment that links routinely collected he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…This data study was supported by PIONEER, 21 a Health Data Research Hub in Acute Care, with ethical approval provided by the East Midlands – Derby REC (reference: 20/EM/0158) and the requirement of informed consent waived. The findings are reported as per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This data study was supported by PIONEER, 21 a Health Data Research Hub in Acute Care, with ethical approval provided by the East Midlands – Derby REC (reference: 20/EM/0158) and the requirement of informed consent waived. The findings are reported as per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The research question and topic were agreed following patient/public discussion groups about NHSE discharge policies. Patients/public reviewed the data fields included in the study, with the PIONEER Data Trust Committee providing support for the project (a group of patient/public members who review studies using health data 9 ). A patient/public group has reviewed the results and has written a lay summary for study dissemination to patient groups.…”
Section: Methodsmentioning
confidence: 99%
“…The profile of NHS users is therefore highly representative of the whole, diverse UK population. Second, alongside other similar initiatives in the UK [22 ▪ ], it is based on routinely collected healthcare data and is approved to be undertaken on an ‘opt out’ basis. Numerous studies have shown that the majority of the UK population supports the use of their health data for research [23,24 ▪▪ ], with fewer than 6% of the UK population having opted out after considerable media coverage of the issue and public awareness [25].…”
Section: Principlesmentioning
confidence: 99%